Regulatory measures to fight obesity in Small Island Developing States of the Caribbean and Pacific, 2015 – 2017 - Nicole Foster; Anne Marie Thow; Nigel Unwin; Miriam Alvarado; T. Alafia Samuels (Revista Panamericana de Salud Pública, 2018)
This report examines the experiences of Small Island Developing States in the Caribbean— Barbados, Dominica, Jamaica, and in the Pacific— Fiji, Nauru, and Tonga with specific governmental regulatory measures to reduce the risk of obesity and associated diet-related chronic noncommunicable diseases (NCDs), as well as the obstacles and opportunities encountered. Guided by the diet-related indicators of the World Health Organization (WHO) Noncommunicable Diseases Progress Monitor 2017, the authors reviewed legislation, country reports, articles, and the databases of WHO and the World Trade Organization to identify relevant regulatory measures and to establish the extent of implementation in the selected countries. Obesity prevalence ranged from 25.9% in Dominica to 41.1% in Tonga. The principal diet-related measures implemented by the selected countries were fiscal measures, such as sugar-sweetened beverage taxes and import duties to encourage greater consumption of healthy foods. Governmental action was weakest in the area of restrictions on marketing of unhealthy foods. If they are to reduce their current high rates of obesity and associated NCDs, Caribbean and Pacific states need to intensify implementation of diet-related regulatory measures, particularly in the area of marketing of unhealthy foods and beverages to children. Key implementation challenges include financial and staffing constraints and the need for increased political will to counter industry opposition and to allocate adequate financial resources to keep advancing this agenda.